Environmental controls on the development of Mississippian microbial carbonate mounds and platform limestones in southern Montagne Noire (France). Issue 6 (15th May 2019) - Cózar, Pedro; Izart, Alain; Somerville, Ian D.; Aretz, Markus; Coronado, Ismael; Vachard, Daniel
Abstract: Late Mississippian carbonates in southern Montagne Noire are dominantly domical to laterally‐accreted microbial mounds in some formations, as well as stratiform microbial limestones occurring in hundreds of olistoliths within a flysch basin, constituting pieces of a giant puzzle that are used to help reconstruct a platform in a region that is no longer preserved. Petrographic data of limestone samples from 14 continuous long sections of olistoliths have been analyzed statistically, using multivariate clustering (Q‐mode) of the components/matrix/cement and canonical correspondence analysis that allow the reconstruction of the environmental parameters of carbonate microbial communities in space and time. Clustering analysis separated microbial and non‐microbial facies. The calculation of indices along the various axes from canonical correspondence analysis allows recognition of the controlling factors of the mounds and microbial growth as being turbidity, light penetration, bathymetry and storms. Turbidity and light penetration are the primary factors controlling the morphology of the microbial limestones. Representation of the light penetration and bathymetry indices on the stratigraphical sections defines two vertical environmental gradients. Light penetration can be subdivided into euphotic, euphotic–dysphotic and dysphotic‐aphotic conditions. The representation of the bathymetry allows the subdivision of samples into a deeper outer ramp, external mid‐ramp and internal mid‐ramp. The curve distance from the section base = f (index) suggests a cyclicity for the platform that cannot be compared with the onlap curve defined from other cratonic areas (Moscow Basin), and thus the cyclic succession of the Montagne Noire is interpreted to have been mostly tectonically‐controlled. Integration of the data allowed the reconstruction of the original Mississippian carbonate platform, where, up to the Mikhailovian, it appears to correspond to a platform morphology, with narrow shallow water facies and wide turbiditic systems, whereas the width of shallow‐water settings expanded during the Venevian to the Protvian, forming a ramp or distally‐steepened ramp with widespread microbial limestones.